Application of the torque equilibrium method in the study of offset displacement in the upper and lower dies in a shearing-cut progressive die. (1st January 2001) - Lin, Zone-Ching; Chang, Jenq-Maw
A shearing-cut progressive die is formed by arranging two or more sets of independent engineering dies in various engineering stations. The design of the shearing-cut progressive die involves a large number of variables. For example, the confirmation of the pressure centre of the shearing-cut progressive die is an issue worthy of exploration and evaluation. In this paper, we use the torque equilibrium method of the upper and lower dies of the shearing-cut progressive die along both sides of the centre axis to derive the pressure centre position of the shearing-cut progressive die. In the past, the search for the pressure centre of dies has not been analysed by more efficient methods. The designed die had to be adjusted step by step to derive the position closer to the pressure centre. Based on these disadvantages, we used the torque equilibrium method of the upper and lower dies along both sides of the centre axis in the search for the pressure centre. The offset displacement of upper and lower dies around the centre is applied to reduce the torque difference on both sides, which further reduces the arrangement time of the upper and lower dies and increases the design capabilities of the shearing-cut progressive die.